PREDIKSI INTERAKSI SENYAWA AKTIF BIDARA (Ziziphus mauritiana) SEBAGAI ANTIKANKER TERHADAP PROTEIN HER2 - Nur Haniyyah Muslimah; Rizki Nur Wijayanti; Dewi Putriarti; Hidayatul Lailiyyah; Erlix Rakhmad Purnama (FMIPA : Universitas PGRI Adi Buana, 2022)
Cervical cancer is a type of cancer that occurs in the cervix which is characterized by the presence of massive tissue cells that grow continuously and are not limited to the cervix and more than 90% are caused by HPV infection. Cervical cancer is in second place at 10.69% after breast cancer at 19.18%. Various efforts have been made to minimize cervical cancer but are inversely proportional to the effects on the body. On the other hand, Indonesia is rich in flora diversity, one of which is the bidara plant (Ziziphus mauritiana) which can produce fruit and has the potential as an anticancer. The purpose of this study was to determine the interaction of the active compound Ziziphus mauritiana on HER2 as an anticancer computationally. The research was conducted using online web databases including the PubChem web, PDB, and software including PyRx, AutoDock, PyMOL, and Discovery Studio 2021. The results of the study were the interaction of the active compound Ziziphus mauritiana against HER2 with PDB code: 6TFZ as a computational anticancer, namely clindamycin with the value of biding affinity is -7.6 kcal/mol; levetiracetam and nonanoic acid with a binding affinity value of -4.8 kcal/mol were rated lower as cervical anticancer compared to trastuzumab with a binding affinity value of -8.8 kcal/mol. Keywords: Cervical cancer, computing, Ziziphus mauritiana